Kebertahanan Usaha Kain Batik di Desa Gulurejo Tahun 1986-2018 - Malibari, Bima Alqari; Putu Mahyuni, Ida Ayu; Girindra Wardani, A.A.A. Dewi (Humanis; Vol 24 No 4 (2020)DO - 10.24843/JH.2020.v24.i04.p13, 2020)
This research entitled The Development of Batik Fabric Enterprises in Gulurejo Village, Lendah District, Kulon Progo Regency, Yogyakarta Special Region 1986-2018. The purpose of this research is to determine the development of batik fabric business in the village of Gulurejo, what factors influenced the development of the batik fabric business and the implications of the development of batik fabric business for the local community. In this the researcher apply the methodology of economic history. The theory used in this research is the theory of Jhon Adam Smith about demand and supply, besides that the researcher also use the theory of commodification from Marx. The method used in this research is historical research method, where in this method there are four stages namely, (1) heuristic, (2) Source Criticism, (3) interpretation, and (4) historiography. The results of this study revealed the ups and downs of the batik cloth business were influenced by several events such as the economic crisis, the Bali bombings and the earthquake. The development of batik cloth business is influenced by the community and government policies. With the development of the batik cloth business until 2018 it has had an impact on society in the socio-economic and socio-cultural fields.